South Africa vs. Australia - What is the score? - Ian Couper (South African Family Practice)
This paper looks at general practice in Australia from a South African's perspective. lt focuses on some of the advantages and disadvantages of the National Heath lnsurance Scheme, which is the cornerstone of health care in Australia. Other issues discussed are the status of general practice, general practice training, the role of hospitals, and the Aboriginal Health Service.